Hinge Flap of Rectus Abdominis Muscle Combined with Component Separation Technique: Clinical Cases. Issue 9 (22nd September 2021) - Aldana, Celso A.; Caceres, Heidi; Gimenez, Alejandro; Saguier, Guillermo
Abstract : Summary: Some techniques to reconstruct the abdominal wall have been published, including the component separation procedure. The contribution of the rectus abdominis flap in the reconstruction of a giant incisional hernia is reported. The authors report three clinical cases in which the component separation technique was insufficient to reconstruct a giant midline incisional hernia. As a salvage technique, the rectus abdominis flap was dissected in the form of a hinge. The postoperative period was successful in all patients, combining both techniques. The rectus abdominis hinge flap could be used as a complementary technique to component separation to reconstruct a giant midline incisional hernia. There are several options to reconstruct the abdominal wall, such as anterior transposition of the posterior rectus sheath, 1 or rotation of the anterior sheath toward the midline. This strategy is known as open book. 2 The rectus turnover flap is also used. 3 The anterior component separation technique closes defects less than 20 cm width. 4 If it is wider, the reconstruction is more difficult. When the operative plan fails in the operating room, an additional technique should be considered. We report on the cases in which we use the rectus abdominis hinge flap.